Ageless Aging : A Woman's Guide to Increasing Healthspan, Brainspan, and Lifespan - Dychtwald, Maddy, 1952-; Hanley, Kate (Rochester, Minnesota : Mayo Clinic Press, 2024)
"We are in the midst of a longevity revolution. And thats particularly true for women: Women can expect to live five years longer than men. A 50-year-old woman can expect to live another 35 years, on average. Women comprise 80% of centenarians, now the fastest growing segment of the worlds population. But despite these incredible statistics showing how women are living longer, women are not living well. Women typically spend the last 14 years of their lives in a cascade of poor health. And while current research suggests that some 70 to 90% of your health and longevity is under your control, rather than at the mercy of the genes you were born with, the reality is that most women are not taking advantage of the measures that could lead to a longer and better life. Ageless Aging presents a pioneering new way for women to age-an ascent that includes feeling youthful and vital while gaining wisdom, resilience, and experience. It provides a holistic plan that helps women take advantage of the scientific, medical, psychological, and spiritual tools available to them as they grow older. Sections include cutting-edge information on the body-fitness, food as medicine, sleep, and hormones-and the science of living longer. It explains the truth about the bodys role in the recipe for longevity, debunks long-held myths around healthcare and health products, and presents the relatively new concept of "precovery." Women are at the forefront of the longevity revolution and they need a trusted resource to help them thrive in old age. With her finger on the pulse of all the research, science, and information about longevity, aging, and the specific issues women face, Maddy Dychtwald is the perfect guide. She understands that Ageless Aging is a process, that the various pieces of the puzzle work synergistically, and with this book she shows you how take control of what you can control to create your best future self. Using stories and examples, Ageless Aging will answer how we: Can fight back against our youth -obsessed culture that conspires against older women Amplify the power of the gifts of aging Match our healthspan to our lifespan Supercharge our immunity Learn the truth about exercise and its role in ageless aging Clear up the confusion about nutrition and supplementation Take steps to potentially prevent or delay cognitive decline Supercharge our brain power Create a more ageless mindset Find the purpose of our longevity bonus years Prepare to make use of our longevity bonus years with maximum impact Create more financial freedom and security for a longer life Take action to transcend age and create super longevity"--
Keywords: Older women -- Health and hygiene; Popular works; Longevity -- Popular works; Holistic medicine -- Popular works; Promotion of Health